A review on shoreline detection framework using remote sensing satellite image - Zulkifle, Farizuwana Akma; Hassan, Rohayanti; Kasim, Shahreen; M. Othman, Razib (UTM Press., 2017)
Shoreline is usually defined as the intersection of the land with the water surface of the mean high water line with the beach profile. In relation, most research in recent years has set the focus on remote sensing which makes it possible to collect data on this shoreline areas. Furthermore, shoreline detection is the ability to recognise and evaluate shoreline detection, so that facilitates decision makers to adapt, mitigate and manage the shoreline risks. Thus, this paper aims to investigate current works on shoreline detection framework using remote sensing satellite images. This investigation includes current research trends on the computational method in shoreline detection, image segmentation, and image filtering method.